Building management system in WebBIM environment - Shkundalov, Danylo; Vilutienė, Tatjana (International Conference “Environmental Engineering”, 2020)
Geographical information systems (GIS) and Building information modelling (BIM) provide digital representation of building, its elements and environment. BIM focuses on micro-level representation of buildings and its elements, and GIS provide macro-level representation of the external elements of environment. Their combination can provide a comprehensive view of a built environment based on integrated data. There is an opportunity to make BIM and GIS unity not only to combine them in a single project but also to make a fully merged environment with difficult associations that extend the capabilities of both. Paper presents method that allows visualization and processing the BIM model in the web browser, external processing and analyzing, easy sharing and visualization, linking the 3D model and attribute information, working with the BIM model and GIS data, digital City mapping and etc. The developed method creates rich future for full BIM software products with all manner of functions and tools that will work through the Internet without installations, distributives, additional programs. The introduced technique can be used as a new part for BIM execution planning.
Keywords: 3D model; GIS; BIM; WEB; WebGL; coordinates; conversion